2022
DOI: 10.3390/cells11172673
|View full text |Cite
|
Sign up to set email alerts
|

miR-200c-3p, miR-222-5p, and miR-512-3p Constitute a Biomarker Signature of Sorafenib Effectiveness in Advanced Hepatocellular Carcinoma

Abstract: Background: Sorafenib constitutes a suitable treatment alternative for patients with advanced hepatocellular carcinoma (HCC) in whom atezolizumab + bevacizumab therapy is contraindicated. The aim of the study was the identification of a miRNA signature in liquid biopsy related to sorafenib response. Methods: miRNAs were profiled in hepatoblastoma HepG2 cells and tested in animal models, extracellular vesicles (EVs), and plasma from HCC patients. Results: Sorafenib altered the expression of 11 miRNAs in HepG2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…De la Cruz-Ojeda investigated the relationship between three sorafenib-deregulated miRNAs (miR-200c-3p, miR-222-5p, and miR-512-3p) and sorafenib response in advanced HCCs. Notably, a hazard ratio analysis showed an association between miR-200c-3p baseline levels and increased survival, while miR-222-5p and miR-512-3p levels, analyzed one month after sorafenib treatment, were associated with a poorer prognosis [120]. Since miR-221 and miR-222 belong to the same bicistronic cluster, findings between that study and ours seem discordant, pointing out that further efforts need to be put in place to obtain robust data that can be translated into laboratory tests, in terms of methodology and evaluation of different patient cohorts.…”
Section: Noncoding Rnas As Biomarkers Of Treatment Response In Hccmentioning
confidence: 98%
“…De la Cruz-Ojeda investigated the relationship between three sorafenib-deregulated miRNAs (miR-200c-3p, miR-222-5p, and miR-512-3p) and sorafenib response in advanced HCCs. Notably, a hazard ratio analysis showed an association between miR-200c-3p baseline levels and increased survival, while miR-222-5p and miR-512-3p levels, analyzed one month after sorafenib treatment, were associated with a poorer prognosis [120]. Since miR-221 and miR-222 belong to the same bicistronic cluster, findings between that study and ours seem discordant, pointing out that further efforts need to be put in place to obtain robust data that can be translated into laboratory tests, in terms of methodology and evaluation of different patient cohorts.…”
Section: Noncoding Rnas As Biomarkers Of Treatment Response In Hccmentioning
confidence: 98%
“…Exosomal miR-30d is highly expressed in the sorafenib effective patients and thereby maybe serve as a predictive biomarker for the efficacy of sorafenib in HCC ( Kohno et al, 2020 ) . MiR-200c-3p, miR-222-5p and miR-512-3p constitute a biomarker signature of sorafenib effectiveness in advanced HCC ( de la Cruz-Ojeda et al, 2022 ). The baseline miR-200c-3p level is correlated with increased survival, whereas increased miR-222-5p and miR-512-3p levels at 1 month after sorafenib treatment are related to poor prognosis.…”
Section: Exosomes In Hcc Diagnosis and Prognosismentioning
confidence: 99%
“…Finally, the active complex interacts with the 3′-UTR of target mRNA through complementary pairing of base pairings, causing translational repression or RNA degradation (Figure 1A). 83−85 Through this process, miRNAs were involved in a series of cellular processes, including apoptosis, 4−6 oxidative stress, 7 cell proliferation, 8,9 inflammation, 10,11 hematopoiesis, 4,12 and tumorigenesis. 13,14 Recent studies revealed that miRNAs not only have an intracellular function but also stably exist in biological fluids such as saliva, cerebrospinal fluid, plasma, serum, gingival fluid, and urine.…”
Section: Micrornasmentioning
confidence: 99%
“…These functional miRNAs form the RISC via binding to AGO. Finally, the active complex interacts with the 3′-UTR of target mRNA through complementary pairing of base pairings, causing translational repression or RNA degradation (Figure A). Through this process, miRNAs were involved in a series of cellular processes, including apoptosis, oxidative stress, cell proliferation, , inflammation, , hematopoiesis, , and tumorigenesis. , …”
Section: Micrornasmentioning
confidence: 99%
See 1 more Smart Citation